Rare giant perianal smooth muscle tumor: A case report - Yuanchao Guo; Yi Song; Xiaona Li; Houhua Liu; Tao Wei; Maowei Yang; Chaonan Zhang; Xingang Li (Journal of International Medical Research)
Smooth muscle tumors are benign tumors originating from smooth muscle tissues, mostly occurring in the uterus and digestive tract; however, smooth muscle tumors occurring in the perianal sphincter are very rare. A 48-year-old woman presented with perianal swelling and pain and was misdiagnosed with a perianal abscess after examination at a foreign hospital. Upon further examination, the patient was diagnosed with a perianal smooth muscle tumor, with a size of approximately 6.5 × 5.5 × 4 cm. We succeeded in surgically removing the tumor. The patient was followed up for 2 years after the operation, and her anus functioned well without recurrence. Perianal abscess and perianal smooth muscle tumors are difficult to differentiate in the clinic and need to be identified via imaging. In clinical practice, smooth muscle tumors should be differentiated from perianal abscess and diseases such as rectal mesenchymal tumors and smooth muscle sarcomas.